Processuell editionsplikt - En undersökning av den processuella editionspliktens förhållande till skyddet av personuppgifter - Sveger,Gabrielle (2024)
The procedural duty of disclosure enables a party, with the assistance of the court and under certain conditions, to compel the opposing party or a third party to produce written documents that may be deemed significant as evidence in an ongoing trial. Much has been written about the procedural duty of disclosure. Nevertheless, the legal landscape remains unclear in many respects. In recent years, the Supreme Court has adjudicated several cases where the conditions for granting the procedural duty to disclose under Chapter 38, Section 2 of the Swedish Code of Judicial Procedure have been subject to examination. On December 29, 2023, the Supreme Court also issued a decision in case NJA 2023 s. 1133 “Personalliggaren” where the issue of procedural duty of disclosure in relation to EU data protection legislation was raised. In this case, the Supreme Court chose to seek a preliminary ruling from the Court of Justice of the European Union (C-268/21 Norra Stockholm Bygg) and posed several questions concerning the relationship between the Swedish provisions on procedural duty of disclosure and the General Data Protection Regulation (GDPR). The thesis investigates the procedural duty of disclosure, with a particular focus on how it relates to the protection of personal data and GDPR. For the court to grant a claim for procedural disclosure, it is required that the opposing party or a third party actually possess the requested documents, that the documents have been sufficiently identified in the order for production of documents, that the requirement of evidentiary relevance is fulfilled, and that the balance of interest between the relevance of the evidence and the opposing party's interest in not disclosing the information must favor the party requesting the disclosure. The scope of the procedural duty of disclosure has evolved in several respects in recent years through case law. Adaptations from the courts' side have been necessary in light of technological developments and can be said to have expanded the conditions for granting disclosure in several aspects. For example, the procedural duty of disclosure encompasses not only written documents but also electronically stored documents and data and providing those document and data in electronic form. The manner in which the court shall address the right to protection of personal data and the provisions of the GDPR in relation to a disclosure request when the requested documents contain personal data has been clarified in the Norra Stockholm Bygg case. The court shall assess an order for production of documents against the provisions regarding lawful processing of personal data and the fundamental principles of the GDPR. The court is required to have regard to the interests of the data subjects concerned in the proportionality assessment that must be conducted. However, strong reasons seem to be required for a an order for production of documents to be rejected because of the privacy interests of the data subjects. Instead, the right to effective judicial protection and a right to a fair trial, which includes the parties to civil court proceedings must be in a position to access the evidence necessary to establish to the requisite standard the merits of their complaints, weighs heavily in the balancing of interests, carries considerable weight during a proportionality assessment. The court also needs to consider in the future whether protective measures, such as masking, need to be taken to safeguard the interests of the data subjects when only some of the personal data are necessary for evidentiary purposes.
Keywords: civilrätt; EU-rätt; processuell editionsplikt; dataskyddsförordningen; skyddet av personuppgifter; procedural duty of disclosure; GDPR